Artesunate versus artemether for the treatment of recrudescent multidrug-resistant falciparum malaria. - Price, R; van Vugt, M; Nosten, F; Luxemburger, C; Brockman, A; Phaipun, L; Chongsuphajaisiddhi, T; White, N (1998)
The therapeutic efficacy and toxicity of artesunate (2mg/kg/day for five days, then 1 mg/kg/day for two days: total=12 mg/kg) was compared with that of artemether (4 mg/kg followed by 2 mg/kg/day for two days, then 1 mg/kg/day for four days: total=12 mg/kg) for the treatment of recrudescent multidrug-resistant falciparum malaria in an open randomized trial in 443 patients living on the western border of Thailand. Parasite and fever clearance times were similar in both groups; within 48 hr 94% (95% confidence interval [CI]=91-96%]) of the treated patients were aparasitemic and 93% (95% CI=89-96%) were afebrile. Symptom resolution and resolution of hepatomegaly were slightly slower in the artesunate group; adjusted hazards ratio=1.5 (95% CI=1-2.0, P < 0.01) and 2.2 (95% CI=1.4-8, P=0.04), respectively. There was no significant difference in times to resolution or development of anemia or splenomegaly between treatment groups. By day 28, 3% (95% CI=0.3-5%) of the patients treated with artesunate and 6% of those treated with artemether (95% CI = 2-9%) had recurrent infections (P=0.3). Both regimens were very well tolerated, with no significant adverse effects attributable to either derivative. Overall, these data suggest that the two oral artemisinin derivatives are safe, highly effective, and result in equivalent therapeutic responses in the treatment of drug-resistant falciparum malaria.